Production and Economic Feasibility of Hydroponics Maize Fodder on Performance of Piglets - Upreti, Sujaya; Ghimire, Ram P.; Tiwari, Megh Raj; Banskota, Niraj (Nepal Journal of Science and Technology, 2021)
An experiment was conducted to evaluate the effects of hydroponics maize fodder on growth and nutrient digestibility of weaned piglets from July 1st, 2017 to August 11th, 2017, for six weeks. The experiment consisted of 75 days old, 15 crossbreed piglets (Duroc x Nagpuri & Duroc) in a Completely Randomized Design with three treatments and five replications. Treatment 1 (T1) contained 100% concentrate feed, Treatment 2 (T2) 90% concentrate feed and 10% hydroponics maize fodder and Treatment 3 (T3) 80% concentrate feed and 20% hydroponics maize fodder in the diet. The study revealed that hydroponics maize fodder contained DM 13.80%, CP 12.54%, NDF 47.04%, and ADL 16.51%. The treatments had non-significant effect (P > 0.05) on daily weight gain, final weight and feed conversion ratio of the piglets. However, piglets fed with 90% concentrate and 10% hydroponics maize fodder had the highest final weight (35.8±5.0 kg), while the lowest (33.6±5.00 kg) was recorded in piglets fed with 80% concentrate and 20% hydroponics maize fodder. The cost of hydroponics maize fodder production was Rs. 20.62 per kg, which was higher than the cost in the Indian context. The difference in Feed Conversion Ratio (FCR) was also not significant. However, piglets fed with T2 (1:2.58) diet recorded higher FCR than T3 (1:2.56) and T1 (1:2.51). In conclusion, the inclusion of hydroponics maize fodder in piglets diet appeared promising in growth, nutrient digestibility and cost of production.